Effect of the Use of Pycnanthus angolensis and Different Supplements on Yields and on the Proximate Composition of Pleurotus sajor-caju. (18th November 2014) - Fakoya, Soji; Adejumo, Abiodun Felix; Akinyele, Julliet Bamidele
Abstract : This study was undertaken with the aim of determining the growth, yield, and proximate composition of Pleurotus sajor-caju cultivated on Pycnanthus angolensis sawdust supplemented with 0, 5, 10, 15, and 20% palm kernel cake (PKC), oil palm fibre (OPF), rice bran (RB), wheat chaff (WC), and corn cobs (CC). P. sajor-caju harvested produced maximum yield of 31.22 g on P. angolensis sawdust supplemented with 15% wheat chaff. The biological efficiency of substrates used ranged from 6.09% to 37.39%. Results also showed a maximum crude protein of 26.33% of P. sajor-caju cultivated on P. angolensis sawdust without any supplement and fat content ranging from 0.25% to 2.21%. Fibre content of harvested mushrooms ranged from 5.05% to 9.29%. The study revealed that supplementing P. angolensis sawdust significantly influenced the growth, yield, and proximate compositions of P. sajor-caju .